Ethanolic extract of Brucea javanica inhibit proliferation of HCT-116 colon cancer cells via caspase activation - Bagheri, Elham; Hajiaghaalipour, Fatemeh; Nyamathulla, Shaik; Salehen, Nur'ain (Royal Society of Chemistry, 2018)
Brucea javanica (L.) Merr. is a well-known plant in Chinese System of Medicine. Its fruits and seeds have been reported to possess curative properties against various ailments. The chemical constituents and biological activity of this plant have been an interesting area in plant and chemistry medicine. The aim of this study is to evaluate the antiproliferative effects of the B. javanica extract against a colon cancer cell line and identification of the chemical components derived from the extract. An ethanolic extract from B. javanica fruits was prepared by cold maceration method, subjected to LC-MS profiling to elucidate the composition abbreviated as BJEE. The extract was screened for the cytotoxicity effects on HCT-116 colon cancer cells via MTT and LDH methods. Additionally, AO/PI staining verified apoptosis features in HCT-116 cells through microscopic analysis. ROS, caspase activity, and gene expression has been performed to identify its possible mechanism of actions which contribute to apoptosis. Output data from this study showed BJEE inhibited the cell proliferation of HCT-116 colon cancer cells at IC50 value of 8.9 ± 1.32 (μg mL-1) and significantly increased the levels of caspase-8, 9, and 3/7 in treated cells in comparison to untreated. The changes in expression of caspase genes and some apoptosis genes like Bax and Bcl-2 were confirmed using RT-PCR. Phytochemical analysis by LC-MS identified six major active compounds (bruceine D, isobrucein A, quassimarin, C16 sphinganine, phytosphingosine, and enigmol) in BJEE that may play a key role in cell apoptosis. The current study showed BJEE could be a promising agent for colorectal cancer therapy by significant increase in caspase activity level, and up-regulation of the specific apoptotic genes.